Transforming rural livelihoods: Tribal women-led agripreneurship under the Farmer FIRST Programme - Yadav, V. K.; Jha, A. K.; Soni, Amrita; Mohan, Prem; Bhadauria, Pragya (Indian Farming, 2025)
The Farmer FIRST Programme (FFP) has significantly enhanced rural livelihoods in the plateau region through resource based interventions and focusing farmer participation and integrating indigenous knowledge with scientific advancements. This participatory approach bridges the gap between researchers, extension workers, and farmers, fostering collaborative problem-solving to overcome the limitations of traditional top-down models. This study highlights the transformative journeys of Smt. Albina Ekka and Smt. Sukarmani Kharkhusa, who adopted integrated farming system and enterprise-based module respectively to diversify income sources and create a roadmap to self-reliance.